Health commodity management information system (Dagu-2 Software) implementation status in public health facilities of South-western Oromia, Ethiopia: a mixed method study - Tadesse Gudeta; Nimona Berhanu; Azmeraw Bekele; Bekele Boche; Tidenek Mulugeta; Gizachew Tilahun; Bodena Bayisa; Julia Kleineidam (BMC Health Services Research)
Abstract Background To ensure the complete traceability of healthcare commodities, robust end-to-end data management protocols are needed for the supply chain. In Ethiopia, digital tools like Dagu-2 are used in the lower levels of the healthcare supply chain. However, there is a lack of information regarding the implementation status, factors, and challenges of Dagu-2, as it is a recent upgrade from the offline Dagu-1 application. Thus, this study aimed to assess the implementation status of Dagu-2 in public health facilities in Southwestern Oromia, Ethiopia. Methods The study employed a sequential explanatory mixed method design to investigate the implementation status of the Dagu2 program in 33 public health facilities in the Southwestern Oromia region of Ethiopia. Study participants were selected using a two-step approach. Firstly, public hospitals and health centers that had implemented Dagu-2 were identified. Secondly, 65 logistic practitioners, including store managers and pharmacy heads, who met the eligibility criteria were selected for the quantitative study. Quantitative data were collected using validated and reliable self-administered questionnaires and analysed using SPSS version 23. We run both descriptive and inferential statistical analyses. Fisher's exact test was used to discern the relationship between dependent and independent variables at p < 0.05. The qualitative data were gathered through in-depth interviews and underwent manual thematic analysis. Results Out of 65 questionnaires, 61 were completed (93.8% response rate). About 77.0% reported using Dagu-2 for operational and strategic decisions, and 80.3% used it for logistics performance monitoring. Roughly 78.7% of the participants indicated a positive implementation status for Dagu-2. Antivirus usage (p = 0.018) and administrative support (p = 0.002) significantly associated with the implementation. External support and user-friendliness facilitated the implementation, while infrastructure constraints, connectivity absence, weak management support, and project handover gaps were major obstacles. Conclusion Overall, the study revealed a promising implementation process and service quality improvements. However, challenges such as lack of management support, limited ICT infrastructure, absence of connectivity, weak management support, and project handover gaps became obstacles for successful implementation. To ensure an effective healthcare system, leveraging technology tools and securing stakeholder support through training are essential.